Silent Soldier : The Man Behind the Afghan Jehad General Akhtar Abdur Rahman Shaheed - Yousaf, Mohammad Brig. 1937- (Lahore, Pakistan Jang Publisher, 1992)
History of General Akhtar's involvement with the Mujahideen during the Soviet occupation of Afghanistan.
Keywords: Afghanistan -- Pakistan -- Generals